A special price just for you: effects of personalized dynamic pricing on consumer fairness perceptions - Anna Priester; Thomas Robbert; Stefan Roth (Journal of Revenue and Pricing Management, 2020)
Personalized dynamic pricing (PDP) involves dynamically setting individual-consumer prices for the same product or service according to consumer-identifying information. Despite its profitability, this pricing provokes strong negative fairness perceptions, explaining why managers are reluctant to implement it. This research provides important insights into the effect of two PDP dimensions (price individualization level and segmentation base) on fairness perceptions and the moderating role of privacy concerns. The results of two experimental studies indicate that consumers perceive individual prices as less fair than segment prices. They also evaluate location-based pricing as less fair than purchase history-based pricing. Consumer privacy concerns moderate these effects.
Keywords: 330; Personalized pricing; Fairness perceptions; Privacy concerns; Dynamic pricing